Effective Time Management Practice And its Role in Organizational Survival:: A Case of Employees from IT Park, Nagpur City of Maharashtra State - Sohail Imran Khan; Bryar Sami Abdulrahman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
To get success and survive in this competitive world, today’s present progressively threatening and rapidly moving organizational environment, organizations need to keep an eye on time productively. Proper time management plays a significant role in increasing productivity and thus the survival of the companies. The current examination explores the effectiveness of time management practice upon organizational survival with special reference to IT park, Nagpur employees. For this research work, the sample size was 103 employees (from total employees of 105) from IT Park, Nagpur City. This sample size was calculated using Taro Yamane’s (1967) formula. The sampling technique used to select samples was simple random. The researcher used Pearson Product Moment Correlation and Percentage Method to analyze the data for hypothesis testing. The investigation exposed to have a noteworthy association between the management of time and employee effectiveness and organizational work performance. Hence, the researcher concluded that employees’ effectiveness and work performance largely depend upon the time management practice in the organization. Secondly, it was also found the presence of a positive effect of time management on the survival of the organization. The recommendations were also made for the decision-makers.